Step-by-Step Development of a Recombinase Polymerase Amplification (RPA) Assay for Sex Identification in Papaya - José Guadalupe Ávila-Hernández; Alejandro Coreño-Alonso; Mario Alberto Pantoja-Alonso; Francisco Javier Córdoba-Andrade; Rogelio González-González; Corina E. Díaz-Quezada; Alberto Camas-Reyes; Agustino Martínez-Antonio (Applied Biosciences)
Papaya is a globally important crop, with production primarily based on hermaphrodite plants. Papaya has three sex types—male, female, and hermaphrodite—determined by flower morphology, but this is only distinguishable at the flowering stage. In this study, a recombinase polymerase amplification (RPA) assay was developed and optimized to identify the three sexes of papaya. Recombinant uvsX, uvsY, gp32, and Bsu DNA polymerase were used to study the effects of temperature, reaction time, and sensitivity conditions for RPA reaction efficiency. The optimal conditions were found to be 41 °C and a 30 min reaction time, allowing the detection of the target sex from specific DNA markers, even when using crude extract. This study shows that RPA could be used for sex determination in papaya, and the findings could contribute to developing a point-of-need strategy due to their sensitivity and specificity.